The last tale of the flower bride ebook A novel. - Chokshi, Roshani (2023)
"A fairy tale in the oldest and truest sense: a haunting dream full of blood and love, vicious truths and beautiful lies. It swallowed me whole, and I went willingly." — Alix E. Harrow, New York Times bestselling author of Starling House "Decadence laced with horror . . . A delightfully meta fairy tale . . . Magic emanates from every exquisitely crafted sentence." — Charlie Jane Anders, Washington Post In the tradition of sumptuous gothic novels like Starling House and The Bloody Chamber comes a dark fairy tale-infused story about a cursed friendship and a marriage steeped in secrets—the breathtaking adult debut from New York Times bestselling author Roshani Chokshi. Once upon a time, a man who believed in fairy tales married a beautiful, mysterious woman named Indigo Maxwell-Casteñada. He was a scholar of myths. She was an heiress. In exchange for her love, Indigo extracted a promise: that her bridegroom would never pry into her past. But when the couple returns to Indigo's childhood home, the House of Dreams, the bridegroom will soon find himself unable to resist. For within the crumbling manor's extravagant rooms lurks the shadow of another girl: Azure, Indigo's dearest childhood friend, who suddenly disappeared. As the house slowly reveals his wife's secrets, the bridegroom will be forced to choose between reality and fantasy, even if doing so threatens to destroy their marriage . . . or their lives. Through a tapestry of secrets woven around dangerous shards of truth, Chokshi crafts an atmospheric fever dream of a novel about love and lies, secrets and betrayal, and the stories we tell ourselves to survive. "Chokshi's tale is as sweet as a piece of fairy fruit, and just as wicked. Every bite is velvet, every swallow is gold, and the taste lingers like a fever dream." — V. E. Schwab, #1 New York Times bestselling author of The Invisible Life of Addie LaRue "Gorgeous and ornate, this sensual fairy tale illuminates the corrosive and redemptive power of both love and lies." — Holly Black, #1 New York Times bestselling author of Book of Night